The association of the type of occupation and obesity among Indonesian workers based on the 2018 Indonesian Food Barometer (IFB) data - Pranoto, Rohmad Joni; Februhartanty, Judhiastuty; Khusun, Helda; Chandra, Dian Novita (World Nutrition Journal, 2024)
Obesity has emerged as one of the global public health challenges. Obesity rates among adults in Indonesia have doubled over the past two decades, including among workers. Obesity among workers can lead to lower productivity and early retirement. Occupational factors have been associated with the prevalence of obesity at the workplace. However, the relationship between occupation type and obesity in Indonesia has not been clarified. Therefore, this study aims to investigate the association between occupation type and obesity among Indonesian workers using data from the 2018 Indonesian Food Barometer (IFB).